Performance Persistance of Southeast Asian Hedge Funds: Empirical Evidence - Shalmanova, Assel (2010)
The study investigates an issue of performance persistence among Southeast Asian long/short equity funds for the period 2000-2008. It has been examined whether hedge funds on the basis of their past performance display persistence over consecutive periods. Using quarterly, half yearly and yearly returns, the hypothesis of no persistence is tested by conventional two-period framework and parametric regression - based methods. It is important to identify winning and losing funds in respect to the time horizon as performance persistence might be sensitive to the periods observed. The results using appraisal ratio suggest that the persistence is strong at shorter as well as longer measurement intervals, whereas alpha and raw return estimation do not show the same implications.